2009
DOI: 10.1002/anie.200904118
|View full text |Cite
|
Sign up to set email alerts
|

Gemini‐Surfactant‐Directed Self‐Assembly of Monodisperse Gold Nanorods into Standing Superlattices

Abstract: Fabrication of ordered nanoparticle assemblies over extended areas and volumes is still a major challenge in nanomaterials research.[1] The current limitations in the production of such ordered assemblies dramatically hinder the application of nanoparticles in fields such as negative refractive index metamaterials or information technologies. In the particular case of metal nanocrystal assemblies, [2] nanoscale organization of readily accessible spherical gold nanoparticles [3,4] has been manipulated to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
159
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 35 publications
(2 reference statements)
5
159
3
2
Order By: Relevance
“…[10] However, ζ of the pT rods in these solvents is found to exceed that of pT-CdSe rods in our study, which implies 1D assemblies should form. Similarly, in reports of orthogonal assemblies in solution of 15 CdSe/CdS and Au-CdSe, the preassembly of the NRs in the bulk solute is critical to vertically aligned order. [7,21] In both cases the equilibrium of dispersion and aggregation was deliberately modulated; 2D monolayers and not 3D supercrystals were formed from assembling NRs in the bulk.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…[10] However, ζ of the pT rods in these solvents is found to exceed that of pT-CdSe rods in our study, which implies 1D assemblies should form. Similarly, in reports of orthogonal assemblies in solution of 15 CdSe/CdS and Au-CdSe, the preassembly of the NRs in the bulk solute is critical to vertically aligned order. [7,21] In both cases the equilibrium of dispersion and aggregation was deliberately modulated; 2D monolayers and not 3D supercrystals were formed from assembling NRs in the bulk.…”
mentioning
confidence: 88%
“…[1] In the case of dispersions of mono-disperse, 15 spherical nanocrystals, the inter-particle interactions can be tuned to form highly ordered supercrystals in the solid state when the correct balance between nanoparticle diffusion rate, solvent volatility and seeding rate is struck. [2] Of recent interest are semiconductor nanorods (NRs) where assembly 20 allows individual properties such as single electron charging, linearly polarised emission and absorption to be collectively tuned and upscaled for application in electronics, photonics and solar energy conversion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A few previous studies have reported the formation of multilayer vertical arrays by decreasing the electrostatic repulsive force via modifying Au nanorods with weak polar ligands instead of cetyltrimethyl-ammonium bromide (CTAB). 20,21 Until recently, there have only been a few reports on the directional self-assembly of CTAB-stabilized Au nanorods into vertically aligned multilayer arrays. 22,23 Recently, our group has shown that it is possible to directly self-assemble CTAB-coated Au nanorods into highly organized vertical monolayer arrays by synergistically controlling the electrostatic repulsive force and the van der Waals attractive force.…”
Section: 19mentioning
confidence: 99%